2021
DOI: 10.3390/cancers13143588
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing DPP-4 Inhibitors for Colorectal Cancer: A Retrospective and Single Center Study

Abstract: Background: There have been studies reporting the crucial roles of Dipeptidyl-peptidase 4 (DPP4) in colorectal cancer (CRC) initiation and progression, whereas DPP4-inhibitors are safe Food and Drug Association (FDA)-approved drugs for treating diabetes. This study aims to investigate the association between DPP4-inhibitor treatment and the prognosis of CRC patients. Methods: Clinical data of CRC patients with diabetes and the prescription of DPP4-inhibitors who had undergone curative surgery in our hospital b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…Actually, CD26 inhibitor, also known as DPP4 inhibitor or gliptin, are a class of oral hypoglycemic drugs that antagonize the enzyme DPP4 and are approved to treat diabetes mellitus type 2 (DM-II). We and others recently reported that CRC patients with concurrent DM-II demonstrated better prognosis when treated with CD26 inhibitors [20][21][22]. Further research on CD26 and its inhibitors is warranted to provide further support for targeting CD26 in CRC treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Actually, CD26 inhibitor, also known as DPP4 inhibitor or gliptin, are a class of oral hypoglycemic drugs that antagonize the enzyme DPP4 and are approved to treat diabetes mellitus type 2 (DM-II). We and others recently reported that CRC patients with concurrent DM-II demonstrated better prognosis when treated with CD26 inhibitors [20][21][22]. Further research on CD26 and its inhibitors is warranted to provide further support for targeting CD26 in CRC treatment.…”
Section: Discussionmentioning
confidence: 84%
“…The immune system plays the most vital role in protection against diseases, including cancer. We previously reported that certain immune cell levels are correlated with the prognosis of post-operative CRC patients [ 24 ]. Hence, in this study, we investigated the association between tumor and NAT CBX8 level with immune cell profile of pre-operative and post-operative blood samples, as well as the dynamic changes in their level between post- and pre-operative blood (expressed as a delta value, which is calculated as post-operative level minus pre-operative level).…”
Section: Resultsmentioning
confidence: 99%
“…An alpha 1-adrenoceptor antagonist, known to treat benign prostate hyperplasia, was reportedly beneficial for blood sugar control [ 35 ]. Furthermore, dipeptidyl peptidase-4 inhibitor (DPP4i) showed promising results in the prognosis of colorectal cancer [ 36 ].…”
Section: Approaches To Drug Repositioning Analysismentioning
confidence: 99%
“…Despite particular cases that benefited from the use of chloroquine, it is difficult to be confident regarding the efficacy of a drug before similar effects are observed in large-scale studies [ 38 , 39 ]. Taking DM as an example, it appears that various antihyperglycemic therapies have other than hypoglycemic effects ( Table 2 ) [ 10 - 12 , 26 , 36 , 40 - 51 ]. In addition, other types of drugs are likely to help lower blood sugar levels in diabetic patients ( Table 3 ) [ 13 , 24 , 25 , 30 , 32 , 35 , 52 ].…”
Section: Considerations For the Introduction Of Drug Repositioningmentioning
confidence: 99%